Utilization Possibility of Cacao Fruit Shell (Theobroma cacao, L) as A Source of Natural Pigment (ï¢- Carotene) - Wulan, Siti Narsito (Fakultas Teknologi Pertanian Universitas Brawijaya, 2001)
The possibility to utilize cacao fruit shell as a source of natural pigment was studied.Â The study included quantitative and qualitative aspects. QuantitativeÂ Â analysis to determine the optimum condition of pigment extraction was done by varying the materials (fresh and dried cacao fruit shell), the concentrations of ethanol as a solvent (75%, 85% and 95%) and the ratios between cacao fruit shell and ethanol (1:1, 1:2, and 1:3).Â The highest concentration pigment extract (as mg b carotene/g material) was given by these conditions:Â fresh cacao fruit shell, ethanol concentration 95% and the ratio 1:3. Qualitative analysis to determine the heat stability of the pigment extract was done by heat treatment in vary temperatures and time exposures (70Â°C, 80Â°C, 90Â°C and 100Â°CÂ forÂ 15, 30, 45 and 60 minutes).Â Pigment degradation was detected by measuring the absorbance in l 435 nm with spectrophotometer analysis.Â Pigment degradation was detected in all temperatures during 30 minutes heat treatment.Â Pigment was also unstable in acid and basic conditions (pH 3, 4, 5, 8 and 9) but stable in neutral condition (pH 7).Â Degradation was occurred when H2O2 (oxidator) andÂ Na2S2O3 (reductor) were added to the pigment extract. Keywords: cacao fruit shell, natural pigment, b- Carotene